A theoretical formulation for the stress analysis of multi-segmented spherical shells for high-volume liquid containment. (15th March 2015) - Zingoni, Alphose; Mokhothu, Batho; Enoma, Nosakhare
Highlights: Presents a formulation for the determination of stresses in multi-segmented vessels. Explains a consistent transfer of membrane forces between adjacent shell segments. Quantifies edge effects based on an accurate bending theory for spherical shells. Validates analytical results of the theoretical formulation via a refined FEM model. Abstract: A linear-elastic theoretical formulation is presented for the complete determination of the state of stress in large thin-walled liquid-filled vessels in the form of multi-segmented spherical shells. The transfer of membrane forces between adjacent shell segments is such that only vertical equilibrium of stress resultants needs to be preserved. The edge effect in the vicinity of the shell junctions is quantified on the basis of an approximate but accurate bending theory for spherical shells. The effectiveness of the developed formulation is demonstrated by consideration of a numerical example. Agreement with the results of finite-element modelling is excellent, showing that the presented theoretical formulation is a reliable, computationally efficient and accurate means of obtaining stresses in large multi-segmented spherical vessels.